Ten types of innovation : the discipline of building breakthroughs - Keeley, Larry (Wiley, 2013)
"Based on over three decades of path-breaking work on innovation effectiveness, [this work] will help you and your teams know what to do when the stakes are high, time is short, and you really to build a breakthrough."--Page 4 of cover